Ash pollen allergy and aerobiology - Gassner, Markus; Schmid-Grendelmeier, Peter; Clot, Bernard (Allergo journal international, 2019)
Background Allergy to ash pollen is common in some parts of Europe. Sensitization is overlooked if Oleaceae pollen allergens are not included in screening tests. Methods Between 1983 and 2007, sensitization to aeroallergens was systematically investigated using serological methods in 15-year-old school children (Immuno-CAP [carrier polymer] test). Samples from 1986 and 2006 were also tested using the immuno-solid-phase allergen chip (ISAC) assay. School children with sensitizations in 1986 were retested in 2010. Airborne pollen concentrations were determined by the Swiss pollen measuring network. Results Sensitization (>0.7 kU/l) to ash pollen ( Fraxinus americana t15)—16.3% (102/627)—was more frequent than to birch pollen ( Betula verrucosa t3): 15.3% (96/627). ISAC assays performed in children in 1986 and 2006 revealed higher molecular seroprevalence for nOle e 1 (15%; 15/100) compared to rBet v 1 (12%; 12/100). Followed-up subjects (age, 39) showed an increase in sensitizations to ash pollen. IgE levels to pollen from indigenous ash ( Fraxinus excelsior t25) were higher than to pollen from American ash ( Fraxinus americana t15). Low ash pollen emission levels were recorded at all measuring sites in Switzerland every 2–4 years. The infection of ashes by Chalara fraxinea resulted in increased emission of ash pollen. Conclusion Symptoms in individuals sensitized to ash pollen vary according to the pollen count and may be masked by pollen from other trees that flower at the same time of year. Sensitization to ash/Ole e 1 can be higher than to birch/Bet v 1. The determination of IgE to common ash ( Fraxinus excelsior ) is more sensitive than to American ash ( Fraxinus americana ). Ash dieback due to Chalara appears to increase pollen emission. Allergies to ash pollen can be significantly underestimated due to a failure to (correctly) identify them; they can also be masked by other pollen families (birch). Harmful organisms such as Chalara can intensify pollen emissions at least temporarily.